Prevalence of Obstructive Sleep Apnea using Stop Bang Questionnaire - An Observational Study - Kalpana A.P,; Kannabiran B,; Franklin Shaju,; Sivakumar S, (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To estimate the prevalence of obstructive sleep apnea (OSA) using the STOP BANG questionnaire in Coimbatore city, Tamil Nadu, India. METHODOLOGY: An observational study was conducted with 203 participants in Coimbatore city from August 2024 to October 2024. A simple random sampling technique was used to recruit the participants. Both males and females aged 18 or older were included in the study. Coronary artery disease, COPD, and anatomical defects of the upper airway were excluded from the study. Informed consent was obtained, and they were asked to complete the STOP BANG questionnaire. The prevalence of obstructive sleep apnea is estimated from the total score obtained on the STOP-BANG questionnaire. Descriptive statistics, such as Mean, Standard deviation, and percentages, were used to analyze the data in this study. RESULTS: The mean age of the participants was 45.6+13.1 years; the mean BMI was 29.1+6.4; The mean neck circumference was 38+8 cm. OSA is more common in males than in females. The prevalence of obstructive sleep apnea is 13.9%. CONCLUSION: This study revealed the prevalence of obstructive sleep apnea, highlighting the importance of public awareness of the disorder and informing management planning.